2021
DOI: 10.1111/jan.14885
|View full text |Cite
|
Sign up to set email alerts
|

The psychological experiences of nurses after inpatient suicide: A meta‐synthesis of qualitative research studies

Abstract: Suicide is a global public health problem. Patients with a range of stressors associated with physical illness, such as physical pain, financial burden and social changes, are at risk for suicide. It was estimated that the suicide rate per 100,000 inpatient years in psychiatric hospitals was 147, which was much higher than the suicide rates in the general community (Walsh et al., 2015). Inpatient suicide is one of the most serious adverse events in both psychiatric as well as general hospitals. After an advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Exposure to risk behaviours facilitated learning and development. However, a variety of negative psychological and physical symptoms were reported, which is consistent with previous reviews (Clua‐García et al., 2021; Hilton et al., 2022; Shao et al., 2021). This Review demonstrated that fear and anxiety around suicide reduced with more experience, but increased exposure to aggression resulted in increased anxiety.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Exposure to risk behaviours facilitated learning and development. However, a variety of negative psychological and physical symptoms were reported, which is consistent with previous reviews (Clua‐García et al., 2021; Hilton et al., 2022; Shao et al., 2021). This Review demonstrated that fear and anxiety around suicide reduced with more experience, but increased exposure to aggression resulted in increased anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…Much of the qualitative research exploring high‐risk behaviours to date focuses on specific interventions of risk behaviours or their impact, and there is limited research capturing the variety of experiences nurses have during these incidents. A recent collection of qualitative systematic reviews on nurses' experiences of either patient suicide (Shao et al., 2021), self‐harm (Clua‐García et al., 2021; O'Connor & Glover, 2017) or aggression (Fletcher et al., 2021) in inpatient settings, all highlighted the negative psychological impact, insufficient training and support that staff experience. Given that nursing staff are likely to experience all of these high‐risk behaviours within their practice, research is needed to develop a novel conceptual framework for how these experiences are collectively understood, which specifically explores how the various high‐risk behaviours converge and diverge in their management as well as their impact on staff.…”
Section: Introductionmentioning
confidence: 99%
“…The scores for each dimension were 0–3 points, with a total score of 0–21. A higher score indicated poorer sleep quality, and a PSQI total score >7 indicated sleep disorder [ 11 ]. The Cronbach's α coefficient of PSQI scale was 0.88.…”
Section: Methodsmentioning
confidence: 99%
“…This support can include managing emotional experiences and self-reflection to develop coping strategies. Furthermore, knowledge about suicide and support to face negative events can be helpful (Shao et al 2021).…”
Section: Discussionmentioning
confidence: 99%